Scale-up of antiretroviral therapy in sub-Saharan Africa – priorities for public health research - Jaffar, Shabbar; Mbidde, Edward; Robb, Alistair; Coutinho, Alex; Muwanga, Moses; Obermeyer, Carla Makhlouf; Weller, Ian; Hart, Graham; Smith, Peter G.; Haines, Andy; Grosskurth, Heiner (Tropical Medicine and International Health, 2007)
The scale-up of antiretroviral therapy (ART) in Africa is the largest health delivery programme ever contemplated on the continent. About 1.3 million people are now on ART and a further 3.5 million are estimated to be in current need of ART. Research is required urgently to identify strategies of scaling-up ART delivery to ensure that it has high coverage, is effective and is available equitably. Furthermore, the number of new infections occurring daily far outstrips the number of patients being placed on ART (World Health Organization, 2007), and to halt the expanding number eligible for treatment, a pressing priority for research is to determine ways of effectively involved in the different components of ART delivery and how should they be trained and supported? What are the costs of ART both to the health services and to the patients? integrating human immunodeficiency virus (HIV) prevention with ART delivery strategies. At present, most government-led ART programmes are based in district or tertiary-level hospitals. This limits the number who can be treated; as hospital services are overburdened, there is a severe shortage of clinical staff, especially physicians, and most hospitals are in urban settings and difficult to access by the majority of people who live in rural areas (Jaffar et al. 2005; Gilks et al. 2006). Home-based care may not be acceptable in many settings because of stigma issues, but it is being evaluated in at least one cluster randomized trial (Jaffar et al., unpublished data). Peripheral health facilities, run by nursing staff or clinical assistants, provide basic primary care in rural communities across Africa. Research is required to determine if ART could be initiated and maintained from such centres. Could the centres monitor patients for side effects from therapy? Could they make referrals to hospitals as and when appropriate? What kind of adherence support and behaviour counselling should the centres provide? How often should patients be followed up and by whom? What should be the minimum cadre of staff